Особливості радіолокаційного виявлення - Шевченко, М. Д. (ХНУРЕ, 2024)
Radar systems have evolved tremendously since their early days when their functions were limited to target detection and target range determination. In fact, the word radar was originally an acronym that stood for radio detection and ranging. Modern radars, however, are sophisticated transducer/computer systems that not only detect targets and determine target range but also track, identify, image, and classify targets while suppressing strong unwanted interference such as echoes from the environment and countermeasures.
Keywords: імпульсний радар; радіолокаційне виявлення